Perspective biotechnology for the reproduction of sheep and goats - S.A.Abbasova; A.I.Mammadova; E.Q. Mustaphayeva (Genius Publishing Group, 2022)
Currently, artificial insemination of sheep and goats is based on spontaneous estrus. As a rule, this technology is very time-consuming and energy-intensive and extends 1,5-2,0 months. One of the ways to intensify the process of reproduction is a biotechnological method of synchronization of the sexual cycle. The use of estrus synchronization technology will allow to change fundamentally the technology of artificial insemination of sheep and goats that will significantly reduce costs and uncrease profitability and competitiveness of the branch. This primarily refers to the peasant (farmer) households and individual part-time farms.
Keywords: sheep; dairy goats; sexual season